Development of Invertebrata Identification Student Worksheet for High School Students - Muhajaroh, Ririn; Pribadi, Tyas Agung; Widiatningrum, Talitha (Journal of Biology Education, 2017)
Invertebrate learning process at SMA N 1 Rembang is dominated by one way learning where the learning process focus on the students in the class, so that it hasn’t made use of the enviroment around them and it hasn’t made the experiment because of the limitation of the media learning.. Because of it, the development of students worksheet which can guide students to do outdoor investigation is needed. The purpose of this study is to determine the feasibility and effectiveness of Invertebrate Identification Students Worksheet for X grade students of Senior High School. The method of this research was Research and Development (R & D) with product of Invertebrate Identification Students Worksheet for High School. Data collection of Students Worksheet for Coastal Invertebrate Identification through 4 stages, including preliminary study, planning, development, and LKS testing. It was found that Student Worksheet (LKS) in Invertebrate Identification is considered effective in supporting outdoor experiment with various assessment among others, quiding students to identify and classify coastal invertebrate.